The Application of Computer Software Technology in the Age of Big Data - Peng, Jiayu (Journal of Theory and Practice of Management Science, 2025)
With the growth of Internet users, mankind has entered the era of big data.The development and application of computer software technology not only improve people's living and office efficiency, but also profoundly affect personal information security.In the era of big data, the application scenarios and scope of computer software have expanded to all aspects of life.This article mainly provides an overview of the current status of computer technology and big data, analyzes the problems existing in software technology in the era of big data, and elaborates on the specific applications of software in the era of big data, in order to better promote software development and serve production and life.